(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
These days, education is more than just traditional classroom instruction. A variety of extracurricular activities are now available to students, with sports being a popular option. In addition to encouraging physical activity, playing school sports like basketball and volleyball helps pupils become more motivated. Examining the difficulties grade 12 students face in juggling their involvement in sports with their academic obligations is the main goal of this study. The researchers also want to find out if playing sports can improve academic achievement. Descriptive correlation research methods were used in a non-experimental qualitative study to gather data on the association between grade 12 students’ academic achievement and their involvement in sports. The study focused on how playing sports can significantly affect a person’s academic performance and involves giving a qualitative survey to a chosen group of respondents. Examining elements like time management, stress reduction, peer pressure, motivation, and rewards was part of this. Statistical techniques, such as descriptive and inferential analysis, were used to further examine the data and ascertain how much sports influence grade 12 participants’ academic achievement. Based on the findings of the study, most seniors in the class participate in sports to a modest degree. Some students participate in sports because they are genuinely excited about them, but others do so because of outside incentives or the apparent academic advantages. Furthermore, some students view sports as enjoyable pastimes that provide them with a way to relax and find fulfillment in their lives. Last but not least, athletes feel that playing sports is essential to improving their performance in the classroom. It is advised that athletes acquire sufficient assistance from their instructors or coaches in order to overcome these obstacles and create a more well-rounded strategy. The purpose of this study is to determine how participation in athletics affects Grade 12 students’ academic achievement at the Bulacan Campus of Bestlink College of the Philippines.